Laipunuk (Nei Ben Lu) – The Last Frontier Of The Taiwan Aborigines During The Japanese Occupation On Taiwan: Ethnographic Narratives Of A Bunun Elder - Martin, Steven Andrew (Penerbit Universiti Sains Malaysia (USM Press), 2011)
The Bunun are one of the indigenous groups of Taiwan that have a rich history of living in the high-mountains. The region of Laipunuk (Nei Ben Lu) was once a group of mountain villages and among the last frontier areas to be annexed into Imperial Japan in Taiwan. The remoteness of the region, coupled with the late arrival of Japanese forces, afforded the Bunun children of that time to have a lifestyle, where they participated in and observed their indigenous way of life. This research is an oral ethnography of Langus Istanda, born in 1920, remembering first hand the arrival of the Japanese police and experienced the forced extradition of her family from their region. The research finds that the informant's childhood memories are generally positive, inasmuch as she tells stories of games, adventures, a safe and comfortable environment, and a sense of wonder for the modernity of the Japanese culture; yet her memories move to a negative tone regarding the forced relocations and the period of illness and death of friends and relatives. The research indicates that the Laipunuk Bunun have endured constant pressure from external forces and, as a direct result, have undergone acute social, cultural, and linguistic degradation from the loss of their native homelands.